Quantitative real-time polymerase chain reaction improves conventional microbiological diagnosis in an outbreak of brucellosis due to ingestion of unpasteurized goat cheese. - Colmenero Castillo, Juan de Dios; Clavijo-Frutos, Encarnación; Morata-Losa, María Pilar; Bravo-Romero, María José; Queipo-Ortuño, María Isabel (Elsevier, 2011)
Rapid diagnosis of individuals involved in brucellosis outbreaks can sometimes be difficult with conventional microbiological techniques. We analyzed, for the first time, the diagnostic yield of a real-time polymerase chain reaction (PCR) assay in a family outbreak of brucellosis due to consumption of unpasteurized goat cheese. PCR correctly identified all symptomatic cases.
Keywords: Brucelosis - Diagnóstico; Reacción en cadena de la polimerasa; Brucellosis; Outbreak; Epidemiology; Diagnosis; Real-time PCR